A Potential Autophagy-Related Competing Endogenous RNA Network and Corresponding Diagnostic Efficacy in Schizophrenia - Li, Rongjie; Wang, Qiaoye; Qiu, Yufen; Meng, Youshi; Wei, Lei; Wang, Hao; Mo, Ruikang; Zou, Donghua; Liu, Chunbin (Frontiers in Psychiatry, 2021)
Competing endogenous RNA (ceRNA) has been implicated in various diseases; in particular, autophagy-associated ceRNA has been linked to neurological diseases. Whether ceRNA also contributes to schizophrenia is unclear. Here we searched public datasets for mRNAs, microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) differentially expressed between schizophrenia patients and healthy individuals. Differentially expressed mRNAs that were related to autophagy were significantly involved in cellular responses to oxygen levels, apoptotic processes, and signaling mediated by Wnt, NF-kappa B, and mTOR. Interactions among differentially expressed miRNAs, mRNAs, and lncRNAs were predicted using TargetScan tools, leading to a potential ceRNA network. Gene set variation analysis (GSVA) scores were derived separately for differentially expressed core lncRNAs, mRNAs or miRNAs related to autophagy. The score based on miRNAs showed an area under the receiver operating characteristic curve of 0.884 for diagnosing schizophrenia. Our results suggest that ceRNA networks contribute to pathophysiology in schizophrenia, and that a GSVA score based on eight differentially expressed miRNAs may help diagnose the condition.